(untitled) (American Journal of Islam and Society, 2003)
In 1997, a group of scholars gathered at the University of Windsor to honor Edward W. Said and his lifetime achievements as a scholar and activist with a conference entitled “Culture, Politics, and Peace.” The present volume, a collection of the papers presented, show just how far reaching his influence has been over the last three decades. While his profound influence on comparative literature and Palestine studies are well known, this volume reveals how his writings have prompted generations of scholars to question takenfor- granted postulations, discourses, and paradigms in literature, area studies, and politics. The papers also applaud his role as an advocate of the Palestinian cause and the way he has tirelessly and critically observed and documented the Palestinians’ fate. The three parts following Richard Falk’s introduction, “Nationalism,” “On Orientalism,” and “To Palestine,” address three dominant themes in Said’s works. In “Empowering Inquiry: Our Debt to Edward W. Said,” Falk celebrates Said’s work as a scholar of many interests and talents, and outlines how his deeply humanist worldview, personal experience as an exile, and critical mind have produced the impressive oeuvre of a leading intellectual of our time. Falk is also the first to mention Said’s emphasis on secularism and his constant critique and warning against bringing religion into the realm of knowledge and politics. This has not prevented Said from defending religious freedom and Muslims in particular, but might have led him to underestimate the moral and intellectual appeal of religious traditions and a religious approach to knowledge. In the case of Palestine and Palestinian politics, his uncompromisingly secular and anti-sectarian views at times make his visions for the future seem incompatible with the region’s realities. Falk points out that Said’s rejection of religion relates to his rejection of absolute truths, or the claim to it, and that he instead chose a “compassionate and engaged rationalism” as his worldview. The section on “Nationalities” starts with Lennard J. Davis’ fascinating essay on “Nationality, Disability, and Deafness,” in which he convincingly argues for the status of deaf people as a nation or community with nation-like features. He explains his work with disability as influenced by Said’s work and engagement in political activism. Davis recalls his personal encounters with Said as a teacher and scholar, and relates his own engagement in advocacy for the deaf to Said’s influence ...